Research on the seasonal variation of zooplankton community in Daya Bay, South China Sea - Wu, Feng-Xia; Gu, Yang-Guang; Liu, Qing-Xia; Zhang, Shu-Fei; Rao, Yi-Yong; Liu, Hua-Xue; Dai, Ming; Wang, Yan-Guo; Huang, Hong-Hui (Frontiers in Marine Science, 2023)
Changes in zooplankton composition, abundance, and some species in response to environmental variation were investigated over four seasons (2020) in Daya Bay. In total, 129 taxa of zooplankton (16 groups of planktonic larvae and 20 indeterminate species) were identified. Zooplankton communities exhibited a significant seasonal shift in abundance and taxonomic composition. The maximum number of zooplankton species was recorded in winter (72 species) and the lowest in spring (42 species). However, the abundance was highest in spring (1,372.01 ± 1,071.14 individuals/m³) and lowest in autumn (50.93 ± 34.05 individuals/m³). Pearson correlation analyses demonstrated that the zooplankton abundance and the variations of indicator species were obviously correlated with environmental parameters (e.g., salinity, temperature, pH, and chlorophyll-a). Based on specificity and occupancy analysis, a total of eight species were selected as indicator species. It is noteworthy that some kollaplankton (such as Dolioletta gegenbauri and Doliolum denticulatum) could potentially cause disaster to the nuclear power plant cooling system because of their relatively large body size and huge blooms in spring. In addition, Centropages tenuiremis blooms in spring and Penilia avirostris blooms in summer could attract assemblages of larval or adult pelagic fish, which would also threaten the cooling system security in Daya Bay. In conclusion, our results suggest that zooplankton communities and some species may be considered as favorable indicators of the marine environment.